Assessing consumer literacy on financial complex products - Rodrigues, L. F.; Oliveira, A.; Rodrigues, H.; Costa, C. J. (Journal of Behavioral and Experimental Finance, 2019)
Consumer financial education has become an important research topic, due to the growth of a wide range of investment products available in online banking. The individuals are exposed to highly complex financial products without understanding the risk and what product is suitable for them. This study investigates and measured the financial education of individuals in complex financial products. A quiz game was developed for a bank website to measure 1597 bank clients in complex products literacy. The survey also enabled a comparison between the basic and advanced skills of financial literacy knowledge. The results highlight a satisfactory overall financial literacy level. While basic knowledge level between individuals has a higher degree, there are serious concerns in advanced skill level. This study contributes to an understanding of adults’ knowledge about the prediction of the risk of investments in complex financial products, as well as providing value to ongoing financial literacy research.